Nonlinear vibrations of cracked reinforced concrete beams - Tan, Chuan Ming (2003)
Although a great deal of work in investigating the possibility of using linear vibration techniques to detect damage in bridges has been carried out over the past 25 years, there are still some major concerns, such as poor sensitivity of modal parameters to damage, requirement of baseline data, need of measuring excitation force as well as environmental effects. Nonlinearity in the vibration characteristics when the structure is damaged further complicates the problem and causes doubts on the feasibility of applying these techniques on actual structures. Understanding of the nonlinear behaviour is therefore crucial. The aim of the work presented herein is to improve the current understanding of the nonlinear vibration characteristics of reinforced concrete beams and to assess its importance to the subject of structural health monitoring of bridges.